2023
DOI: 10.3390/nano13111705
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Adsorption Behavior of SF6 Decomposition Components on Mg-MOF-74

Abstract: SF6 gas is an arc extinguishing medium that is widely used in gas insulated switchgear (GIS). When insulation failure occurs in GIS, it leads to the decomposition of SF6 in partial discharge (PD) and other environments. The detection of the main decomposition components of SF6 is an effective method to diagnose the type and degree of discharge fault. In this paper, Mg-MOF-74 is proposed as a gas sensing nanomaterial for detecting the main decomposition components of SF6. The adsorption of SF6, CF4, CS2, H2S, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…et al showed that a combination of the PBE0 functional and def-tzvp performed best in the geometric optimization of mononuclear platinum complexes based on the DFT principle. In this study, we use the same exchange-correlation functional, basis set, and van der Waals action correction algorithm as in our previous research study [48]. We set the charge to 0 and the spin multiplicity to 1.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…et al showed that a combination of the PBE0 functional and def-tzvp performed best in the geometric optimization of mononuclear platinum complexes based on the DFT principle. In this study, we use the same exchange-correlation functional, basis set, and van der Waals action correction algorithm as in our previous research study [48]. We set the charge to 0 and the spin multiplicity to 1.…”
Section: Calculation Methodsmentioning
confidence: 99%